Deguelin Induces Apoptosis by Targeting Both EGFR-Akt and IGF1R-Akt Pathways in Head and Neck Squamous Cell Cancer Cell Lines. (17th May 2015) - Baba, Yuh; Fujii, Masato; Maeda, Toyonobu; Suzuki, Atsuko; Yuzawa, Satoshi; Kato, Yasumasa
Abstract : Deguelin, a rotenoid compound from the African plant Mundulea sericea (Leguminosae), has been shown to possess antitumor activities but the exact role for the growth factor receptor mediated signaling pathway in head and neck squamous cell carcinoma (HNSCC) is currently still unclear. In the present study, we investigated the effect of deguelin on epidermal growth factor receptor (EGFR) and insulin-like growth factor-1 receptor (IGF1R) pathways in HNSCC cell lines. Flowcytometric analysis revealed accumulation of annexin V positivity in deguelin-treated cells, showing that deguelin induced apoptosis. The deguelin-induced apoptosis was accompanied by the reduction of constitutive phosphorylated levels of IGF1R, Akt, and extracellular signal-regulated kinase1/2 (ERK1/2). LY294002-mediated inhibition of phosphatidylinositol-3 kinase, which is an upstream effector for Akt activation, increased cleavage of poly(ADP-ribosyl) polymerase (PARP) but ERK inhibition by U0126 did not. Deguelin inhibited both IGF-1- and EGF-induced Akt activation. These results showed that deguelin possessed antitumor effect by targeting Akt in dual axis such as EGFR and IGF1R signaling pathways and suggested that it provides an applicable therapeutic strategy for HNSCC patients.